Combined effects of Tai-Chi gait with mediolateral ground support perturbation on dynamic balance control - Jacob Smith; Troilyn Jackson; Wei Liu; Jonathan Gelfond; Hao-Yuan Hsiao (Sports Medicine and Health Science)
Tai-Chi (TC) is a broadly used exercise that appeared to decrease the risk of falls. However, biomechanical mechanisms underlying the reduced fall risks following TC exercise remain unclear and hinder the ability to optimize TC intervention to target specific balance deficit disorders. In addition, combining TC gait exercise with ground support perturbation may be a viable approach to further challenge balance control compared to TC gait alone. The purpose of this study was to compare dynamic stability and limb support force production during comfortable walking speed (CWS), TC gait, and TC gait with medial (MED) and lateral (LAT) ground support perturbations in older and younger adults. Ten older adults and ten younger adults performed CWS, TC gait, LAT, and MED. Conditions involving TC gait showed decreased margin of stability (MoS) (main effect of condition, p ​< ​0.01) and increased vertical force impulse compared to CWS (p ​< ​0.01). Medial ground support perturbation induced the smallest MoS among all conditions. Older adults showed increased MoS compared to younger adults (p ​< ​0.01). These findings provided insight into how key balance control characteristics are modulated during TC exercise and indicate that combining ground support perturbation with TC may further challenge dynamic stability.